2010
DOI: 10.1186/1471-2156-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Male-like sexual behavior of female mouse lacking fucose mutarotase

Abstract: BackgroundMutarotases are recently characterized family of enzymes that are involved in the anomeric conversions of monosaccharides. The mammalian fucose mutarotase (FucM) was reported in cultured cells to facilitate fucose utilization and incorporation into protein by glycosylation. However, the role of this enzyme in animal has not been elucidated.ResultsWe generated a mutant mouse specifically lacking the fucose mutarotase (FucM) gene. The FucM knockout mice displayed an abnormal sexual receptivity with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It also suggests that fucose or its derivatives can be used as potential modulators of behavioral abnormalities observed in IBD. To our knowledge, there is at least one report that links fucose to mouse social behavior [80]. Park and colleagues demonstrated that the lack of fucose mutarotase (FucM), an enzyme that facilitates fucose incorporation into protein [81], resulted in the male-like sexual behaviors in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that fucose or its derivatives can be used as potential modulators of behavioral abnormalities observed in IBD. To our knowledge, there is at least one report that links fucose to mouse social behavior [80]. Park and colleagues demonstrated that the lack of fucose mutarotase (FucM), an enzyme that facilitates fucose incorporation into protein [81], resulted in the male-like sexual behaviors in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding gene transcript, fucose mutarotase, is an enzyme of the fucose-utilization pathway performing the interconversion between α-L-fucose and β-L-fucose on human cell surfaces. Hereof, besides one animal study demonstrating male-like sexual behavior in FUOM knock-out mice, presumably resulting from reduced fucosylation during neurodevelopment (Park et al, 2010), further associations with pathological states in mammals have not been published for this gene. Regarding reward processing, the protein coding DUSP3 (Dual-specificity phosphatase 3) gene, member of the dual-specificity protein phosphatase subfamily, showed strongest correlation with measured fMRI data in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…A promising new approach derives from a recent study of performance-related traits in racing Alaskan sled dogs (68). Racing dogs are divided into distance and sprint categories.…”
Section: Canine Behaviormentioning
confidence: 99%
“…The latter perform short ( < 30 mile) runs, whereas the former race for hundreds of miles over multiple consecutive days, as in the renowned Idi-tarod race. Huson et al studied the genomes of sprint and distance racing dogs and identified purebred signatures within these highly mixed populations associated with specific traits, such as endurance, work ethic, and speed (68). Follow-up GWAS studies are now in progress to identify the underlying genes.…”
Section: Canine Behaviormentioning
confidence: 99%